(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
The indoor air pollutants in student hostel room during eight different conditions were evaluated. One minute interval of TVOC, CO2, CO, O3 concentrations, temperature and relative humidity were measured inside a vacant hostel room of Universiti Sains Malaysia. Four fan speeds of 0, 1, 3 and 5 and the installed window being open and close were selected as the basis to determine the condition inside the hostel room. Result suggested that the concentrations of indoor air pollutants were below the maximum permissible values outlined by Industrial Code of Practice on Indoor Air Pollutants except for O3, with maximum concentration are 576 ppb (TVOC), 666 ppm (CO2), 4.4 ppm (CO) and 90 ppb (O3). The hourly trend of TVOC and CO2 concentrations with peak concentrations were observed in the morning (8 a.m.) due to outdoor traffic emission which greatly influenced the indoor pollutants variation. Meanwhile, O3 showed some delay in time to reach peak concentrations that were observed at 4 p.m. and 5 p.m. Result indicate that the conditions set up were incapable in the regulation of indoor pollutants variation since these pollutants are more dependent with the source of emission and destruction factors.